Micro energy harvesting - Briand, Danick; Yeatman, Eric; Roundy, Shad (Weinheim : Wiley-VCH Verlag GmbH & Co. KGaA, 2015)
With its inclusion of the fundamentals, systems and applications, this reference provides readers with the basics of micro energy conversion along with expert knowledge on system electronics and real-life microdevices. The authors address different aspects of energy harvesting at the micro scale with a focus on miniaturized and microfabricated devices. Along the way they provide an overview of the field by compiling knowledge on the design, materials development, device realization and aspects of system integration, covering emerging technologies, as well as applications in power management, e.
3.4.4 Limits3.4.4.1 Parasitic Capacitors; 3.4.4.2 Breakdown Voltage; 3.4.4.3 Pull-In Force; 3.5 Other Electromechanical Transduction Principles; 3.5.1 Electrostrictive Materials; 3.5.1.1 Physical Origin and Constitutive Equations; 3.5.1.2 Energy Harvesting Strategies; 3.5.2 Magnetostrictive Materials; 3.5.2.1 Physical Origin; 3.5.2.2 Constitutive Equations; 3.6 Effect of the Vibration Energy Harvester Mechanical Structure; 3.7 Summary; References; Chapter 4 Thermal Fundamentals; 4.1 Introduction; 4.2 Fundamentals of Thermoelectric Power Generation
Includes bibliographical references and index.
Online resource; title from PDF title page (Ebsco, viewed May 1, 2015).
Keywords: Microharvesters (Electronics); Energy harvesting; TECHNOLOGY & ENGINEERING / Electrical; Energy conversion; Energy harvesting; Nanotechnology; Power resources; Energy harvesting; Microharvesters (Electronics); Electronic books; Electronic books